1α, 25-Dihydroxyvitamin D3 up-regulates IL-34 expression in SH-SY5Y neural cells. Issue 7 (October 2017) - Zhang, Dong; Li, Miaomiao; Dong, Yang; Zhang, Xinhui; Liu, Xingyun; Chen, Zhangming; Zhu, Yongji; Wang, Huiming; Liu, Xuwen; Zhu, Jialiang; Shen, Yujun; Korner, Heinrich; et al.
Vitamin D supplementation is regarded as a novel approach to treat Alzheimer's disease, but the underlying mechanism remains elusive. The cytokine IL-34 provides strong neuroprotective and survival signals in brain injury and neurodegeneration and could be an immunological mediator for the vitamin D-induced protection. The aim of this study was to investigate whether human IL-34 is up-regulated in neuronal cells by the hormonally active form of vitamin D, 1α, 25-dihydroxyvitamin D3 [1α, 25(OH)2 D3 ]. We found that IL-34 was detectable in a variety of cell lines and its expression was strongly induced in SH-SY5Y neural cells in a dose- and time-dependent manner by 1α, 25(OH)2 D3 through the vitamin D receptor (VDR). Furthermore, we identified the core promoter of IL-34 gene and a VDR binding site (CGCCCT) that was required for 1α, 25(OH)2 D3 -induced IL-34 expression. These findings suggest that the induction of IL-34 expression by 1α, 25(OH)2 D3 may constitute a mechanism that explains the protective function of vitamin D in Alzheimer's disease.